RESPON IRAN TERHADAP FILM ARGO - Nidya Utami; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research discusses Iran’s response to the political thriller movie Argo and how the movie represents Iranians. Argo movie was launch in October 2012 focusing on an exfiltration mission in Iran by the CIA, which is based on true events in 1979 when the Islamic Revolution broke in Iran. Iranian in 2012 was shocked by Argo’s Iranian depiction that was deem by president Mahmoud Ahmadinejad ‘anti Iranian’ and American propaganda. Iran further their accusation when Argo receive the prestigious Oscar award handed by first lady Michelle Obama at Febuary 24th 2013. This research will explain the Iran Hostage Crisis and Canadian Caper history in 1979, how Iran respond to the movie Argo in 2013, the scenes that was protested by the Iranian government, what kind negotiations are being done, and how the movie Argo influences Iran’s and United States international relations. Perspective that used in this research is Realism perspective. The theory used in this research is the mass media concept. The theory used as a framework for analyzing the factors and cause the movie Argo and its consequences for Iran’spolitical situation.Key words: Iran, respond, Argo movie, United States, international relation